The role of aesthetic, cultural, utilitarian and branding factors in young Chinese consumers' repurchase intention of smartphone brands. (February 2017) - Filieri, Raffaele; Lin, Zhibin
Abstract: Despite the exponential growth of smartphone consumption, to date, very few studies have investigated the factors that influence consumers' repurchase intention of smartphone brands. China has become the world's largest consumer markets for smartphones, therefore understanding young Chinese consumers' repurchase intention in the smartphone market is of crucial importance to smartphone companies. A preliminary qualitative study based on 30 face-to-face interviews has led to the development of a new conceptual framework including aesthetic (design appeal), functional (perceived quality), brand value (brand popularity), social (subjective norm) and cultural influences ( mianzi ). The newly developed framework has been tested through partial least squares structural equation modeling with a sample of 321 young Chinese smartphone users. The results show that young Chinese customer's smartphone repurchase intention is mainly determined by mianzi, perceived quality, brand popularity, and design appeal. Furthermore, findings also highlight that subjective norm, perceived quality and design appeal affect Chinese people's mianzi . Graphical abstract: Highlights: This study investigates young Chinese consumers' repurchase intention of smartphone. The study adopts mixed method (interviews + quantitative analysis, PLS-SEM). Develops a new framework including aesthetic, functional, branding, socio-cultural influences. Subjective norm, perceived quality and design appeal influence young Chinese consumers' mianzi . Mianzi, perceived quality, design appeal predict repurchase intentions.